Daily family stress and HPA axis functioning during adolescence: The moderating role of sleep. (September 2016) - Chiang, Jessica J.; Tsai, Kim M.; Park, Heejung; Bower, Julienne E.; Almeida, David M.; Dahl, Ronald E.; Irwin, Michael R.; Seeman, Teresa E.; Fuligni, Andrew J.
Highlights: We examined the interaction between family conflict and demands and behavioral sleep indices on HPA axis function among adolescents. Sleep latency and sleep efficiency moderated the relation between family demands and the cortisol awakening response (CAR). Family demands were associated with a smaller CAR among adolescents with longer sleep latency and lower sleep efficiency. No interaction between family conflict and sleep indices on HPA axis function emerged. Abstract: The present study examined the moderating role of sleep in the association between family demands and conflict and hypothalamic-pituitary-adrenal (HPA) axis functioning in a sample of ethnically diverse adolescents ( n  = 316). Adolescents completed daily diary reports of family demands and conflict for 15 days, and wore actigraph watches during the first 8 nights to assess sleep. Participants also provided five saliva samples for 3 consecutive days to assess diurnal cortisol rhythms. Regression analyses indicated that sleep latency and efficiency moderated the link between family demands and the cortisol awakening response. Specifically, family demands were related to a smaller cortisol awakening response only among adolescents with longer sleep latency and lower sleep efficiency. These results suggest that certain aspects of HPA axis functioning may be sensitive to family demands primarily in the context of longer sleep latency and lower sleep efficiency.